PENGARUH BRAND IMAGE DAN BRAND AWARENESS TERHADAP PURCHASE DECISION LAZUNA CHICKEN PADA MAHASISWA POLITEKNIK NEGERI UJUNG PANDANG - Andi Husnul; Jayadi Jayadi; Ahmadi Usman (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2023)
This study aimed to determine the effect of brand image and brand awareness on purchase decision Lazuna Chicken among students of Politeknik Negeri Ujung Pandang. The samples included 98 respondents selected using purposive sampling technique. Data analysis used descriptive statistical analysis using IBM SPSS 26, with validity and reliability tests, and classic assumption test being employed. The hypothesis in this study is the associative hypothesis where the test used is multiple linear regression analysis, t-test, f-test, and analysis of the coefficient of determination.The results of this study were: (1) brand image had a positive and significant influence on purchase decisions with a sig. 0.040 <0.05 and t-value 11.305 > 1.985. (2) brand awareness had a positive and significant influence on purchase decisions with a sig. 0.000 < 0.05 and t-value of 14.138 > 1.985. (3) brand image and brand awareness simultaneously had a positive and significant influence on purchase decision with a significance level of 0.000 less than 0.05 and F-value 109.452 > 3.092 and R-Square 69.7%.